Escola na contemporaneidade e o sentido humanizador da educação: concepções da Igreja Católica Apostólica Romana - Novais, Luis Eduardo Duarte (2016)
The Roman Apostolic Catholic Church has reiterated that the schooling process must contemplate the etic and religious dimensions of human person with the objective of developing the personal and social responsibilities in opposite to conceptions intervened in utilitarianism and pragmatism. Once the Catholic Cristian vision defines education as the indispensable interlocutor in debates about educational reality, developed by the Ecclesial Magisterium after the II Vatican Council (1962-1965), this research aims to analyze the relation between Catholic Church educational conceptions and it aims to explore the school meaning in contemporaneity. The investigation presents the qualitative approach and exploratory nature, and the methodological procedure is the interpretation of post-council documents elaborated by the Congregation for Catholic Education. The documental analysis to realize the theoretical framework included John Paul II (1982), Edith Stein (2003) e Jacques Maritain (1945, 1967, and 1968). These authors present a unitary conception of human being and they develop the conception that there is not any dualist superposition between their organic-corporeal-psychic nature and religious-spiritual nature. They postulate that the human objective himself through culture and they affirm the education must be occupied of integral formation of everybody, as an essential sociocultural action. It is necessary reflecting about the curricular proposition of school education considering the relation between education and culture as a support to a project of human person development. The theorical fundamentation about curriculum have thinkers as Abramowicz (2006), Apple (2006), Candau (2000, 2014), Forquin (1993, 2000), Goodson (1995), Moreira (2011), Saviani (1996, 2005) and Silva (1995); they study the relation established between education and culture at school with different and conflicting approaches. Rodrigues (2001) systematizes relevant argumentation with the discussion about ethic’s formation of person by the overcoming of the complex axiology crisis that marks the contemporaneity. The results show that it is necessary undertake an integral human formation at school, and it must ensure to student the competence to know himself as a free ethical subject who is responsible for their choices, experiencing his relationship with God, with himself, in interaction with others and the environment